New Broth Macrodilution Volatilization Method for Antibacterial Susceptibility Testing of Volatile Agents and Evaluation of Their Toxicity Using Modified MTT Assay In Vitro - Houdkova, Marketa; Chaure, Aishwarya; Doskocil, Ivo; Havlik, Jaroslav; Kokoska, Ladislav (Molecules (Basel, Switzerland), 2021)
In this study, a new broth macrodilution volatilization method for the simple and rapid determination of the antibacterial effect of volatile agents simultaneously in the liquid and vapor phase was designed with the aim to assess their therapeutic potential for the development of new inhalation preparations. The antibacterial activity of plant volatiles (β-thujaplicin, thymohydroquinone, thymoquinone) was evaluated against bacteria associated with respiratory infections (Haemophilus influenzae, Staphylococcus aureus, Streptococcus pneumoniae, Streptococcus pyogenes) and their cytotoxicity was determined using a modified thiazolyl blue tetrazolium bromide assay against normal lung fibroblasts. Thymohydroquinone and thymoquinone possessed the highest antibacterial activity against H. influenzae, with minimum inhibitory concentrations of 4 and 8 µg/mL in the liquid and vapor phases, respectively. Although all compounds exhibited cytotoxic effects on lung cells, therapeutic indices (TIs) suggested their potential use in the treatment of respiratory infections, which was especially evident for thymohydroquinone (TI > 34.13). The results demonstrate the applicability of the broth macrodilution volatilization assay, which combines the principles of broth microdilution volatilization and standard broth macrodilution methods. This assay enables rapid, simple, cost- and labor-effective screening of volatile compounds and overcomes the limitations of assays currently used for screening of antimicrobial activity in the vapor phase.
Keywords: tropolon; aplikace inhalační; antibakteriální látky; cytotoxicity; Streptococcus pyogenes; volatilizace; Volatilization; Bacteria; Thymol; Monoterpenes; thymol; vapor phase; Anti-Bacterial Agents; macrodilution method; Tropolone; β-thujaplicin; Administration, Inhalation; Staphylococcus aureus; Microbial Sensitivity Tests; volatile compound; antimicrobial; benzochinony; Benzoquinones; thymohydroquinone; těkavé organické sloučeniny; thymoquinone; Oils, Volatile; mikrobiální testy citlivosti; Haemophilus influenzae; monoterpeny; oleje prchavé; Volatile Organic Compounds; Streptococcus pneumoniae; respiratory infections